2016
DOI: 10.1080/15476286.2016.1164365
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-26a/b and their host genes synergistically regulate triacylglycerol synthesis by targeting theINSIG1gene

Abstract: The microRNA-26 (miR-26) family is known to control adipogenesis in non-ruminants. The genomic loci of miR-26a and miR-26b have been localized in the introns of genes encoding for the proteins of the Cterminal domain RNA polymerase II polypeptide A small phosphatase (CTDSP) family. Insulin-induced gene 1 (INSIG1) encodes a protein with a key role in the regulation of lipogenesis in rodent liver. In the present study, we investigated the synergistic function of the miR-26 family and their host genes in goat mam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 58 publications
2
43
0
Order By: Relevance
“…Additionally, functional validation has directly linked a number of miRNAs with regulatory roles in milk synthesis, fatty acid metabolism and cellular differentiation. Down-regulation of miR-26a/b and their host genes ( CTDSPL, CTDSP2 and CTDSP1 ) in goat mammary epithelial cells was shown to decrease the expression of genes related to fatty acid synthesis ( PPARG, LXRA, SREBF1, FASN, ACACA, GPAM, LPIN1, DGAT1 and SCD1 ), triacylglycerol accumulation and unsaturated fatty acid synthesis as well as demonstration of a functional association between miR-26a/b, their host genes and INSIG1 16. MiR-155a was observed to regulate the expression of growth hormone receptor and decrease bovine mammary epithelial cell viability and lactation12.…”
mentioning
confidence: 93%
“…Additionally, functional validation has directly linked a number of miRNAs with regulatory roles in milk synthesis, fatty acid metabolism and cellular differentiation. Down-regulation of miR-26a/b and their host genes ( CTDSPL, CTDSP2 and CTDSP1 ) in goat mammary epithelial cells was shown to decrease the expression of genes related to fatty acid synthesis ( PPARG, LXRA, SREBF1, FASN, ACACA, GPAM, LPIN1, DGAT1 and SCD1 ), triacylglycerol accumulation and unsaturated fatty acid synthesis as well as demonstration of a functional association between miR-26a/b, their host genes and INSIG1 16. MiR-155a was observed to regulate the expression of growth hormone receptor and decrease bovine mammary epithelial cell viability and lactation12.…”
mentioning
confidence: 93%
“…Total RNA was obtained from mammary gland tissue of each goat using the Trizol reagent (Invitrogen, USA) according to the manufacturer's protocol. The expression of the miR-26 family and their host genes was detected with primers reported previously (Wang et al, 2016), and analysed using the 2 -ΔΔCt method. The 5S rRNA was used as reference gene for miR-26 family expression experiment, and mRNA expression was normalized to ubiquitously expressed transcript (UXT), mitochondrial ribosomal protein L39(MRPL39) and ribosomal protein S9(RPS9), all the reference primers used were as reported previously (Wang et al, 2016).…”
Section: Twenty-four Mid-lactation (120 D After Parturition) Xinongmentioning
confidence: 99%
“…The function of a miRNA is ultimately defined by its effects on target genes expression. A previous study showed that the miR-26 family is involved in lipid synthesis in human, goat, and mice (Ning et al, 2017;Song et al, 2014;Wang et al, 2016), but the molecular mechanisms are unclear. To address the question of how the miR-26 family functions in concert with their target genes to provide some molecular insight into the lipid synthesis process, we used PicTar and TargetScan to predict miR-26 family targets.…”
Section: Twenty-four Mid-lactation (120 D After Parturition) Xinongmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this study did not examine adipogenesis or changes in the hormones leptin, insulin, and TNF-alpha 105 . Nonetheless, a number of studies have shown the impact of miRNAs on fatty acid oxidation and lipogenesis 83,106 .…”
Section: Cardiovascular Risk Factorsmentioning
confidence: 99%